Employer Market Power and Wage Dynamics in Malaysian SMEs: Analyzing the Impact of Concentrated Labor Markets - Nedunchelian; Pillay, Narayanasamy (2024)
This paper examines the relationship between employer concentration and wages within small and medium-sized enterprises (SMEs) in Malaysia. It investigates how increased market power among employers affects wage levels and labor market outcomes. By analyzing existing literature and conducting empirical research, we provide insights into the mechanisms through which employer concentration influences wages in the Malaysian SME sector. Our study employs a mixed-methods approach, combining qualitative and quantitative data, to offer comprehensive findings and practical recommendations.